Review Of the Effectiveness and Implementation of The Unified Periodic Tax Return (Coretax) On Government Agency Taxpayer Compliance and Tax Revenue at Tax Office X - Naufal Satria Daniswara; Asqolani Asqolani (IPSAR (International Public Sector Accounting Review), 2025)
This study examines the effectiveness and implementation of the Unification Periodic Tax Return within the Coretax system on the compliance of government agency taxpayers and tax revenue at tax office X. This study employs a qualitative method with data collection techniques through in-depth interviews with Account Representatives and representatives of government agency taxpayers, as well as documentation studies. The results indicate that the Coretax implementation created a "compliance shock," systematically compelling government agencies to become more disciplined through a rigid workflow (tax withholding receipt, report, pay), thereby enhancing reporting compliance. The impact on revenue is more on the acceleration and safeguarding of existing tax potential rather than an absolute nominal increase, whichis tied to budget allocations (DIPA). Key obstacles include technical issues such as delays in SP2D data synchronization, creating a "compliance paradox," an increased manual workload for operators, and a gap between automation expectationsand reality. The efforts of tax office X in providing education and consultation services proved effectivein assisting taxpayers during the transition period.